2021
DOI: 10.1007/s40617-021-00605-4
|View full text |Cite
|
Sign up to set email alerts
|

Animal-assisted Interventions as an Adjunct to ABA Services: Clinician Practices and Perceptions

Abstract: Although the popularity of animal-assisted interventions (AAI) continues to increase, an examination of these practices among clinician populations that may incorporate AAI in their clinical services are largely absent from the literature. This study examined the practices and desirability of incorporating animals into ABA services. A total of 544 ABA clinicians completed a web-based survey. Data revealed respondents not only considered incorporating animals into ABA services (n = 307), but almost 20% (n = 107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…A recent study found improvements in patients' anxiety and self-esteem and showed that participants in AAT programs find it applicable and relevant because the positive results obtained by way of relaxation, fun, or self-knowledge, and the dog-contact experience itself [12]. One remarkable aspect of AAT is the positive valuation by health personnel [13,14] and the high rates of adherence, which could be related to patients' positive perception of such experiences [15].…”
Section: Of 12mentioning
confidence: 99%
“…A recent study found improvements in patients' anxiety and self-esteem and showed that participants in AAT programs find it applicable and relevant because the positive results obtained by way of relaxation, fun, or self-knowledge, and the dog-contact experience itself [12]. One remarkable aspect of AAT is the positive valuation by health personnel [13,14] and the high rates of adherence, which could be related to patients' positive perception of such experiences [15].…”
Section: Of 12mentioning
confidence: 99%